586 The general essential objectives of medical rehabilitation in the management of chronic dyspnea – a systematic review (Balneo and PRM Research Journal, 2024)
Dyspnea is defined by an increased laboured breathing, due to interactions of motor, sensory and metabolic nerve impulses, with increased airway resistance, caused by hypoxemia or hypercapnia. Chronic  dyspnea presents various causes, respiratory disease, cardiovascular disease, skeletal disease, anaemia, obesity or even physical deconditioning, a condition that persists for more than 4–8 weeks. As for the rehabilitation program, it involves the patient’s re-education, the actual physical recovery, change in risk factors and psychological counselling, all leading to the definite improvement of the physical and mental condition, with positive consequences on the quality of life. The rehabilitation programme applied to increase exercise tolerance in patients with chronic  dyspnea can be performed safely; it will also result in an increase in the quality of life of patients. There is a need to develop a strategy for a long-term approach to patients with chronic  dyspnea, involving a multidisciplinary team for the constant follow-up of these patients using easily reproducible, feasible and low-cost methods. Rehabilitation therapy in patients with chronic  dyspnea uses a set of therapeutic measures, with the aim of restoring greater physical and mental capacity than before the programme.